DISCIPLINARY ACTIONS UNDER THE POLICE CODE OF ETHICS FOR OFFICERS INVOLVED IN ADULTERY: A Case Study of the Police Code of Ethics Commission Decision No. PUT/11/XI/HUK.12.10/2023 - Yahman, Yahman; Efendi, Jonaedi; Karim, Karim; Anjani, Shella Devita (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
This research paper addresses the significant issue of disciplinary actions under the Police Code of Ethics concerning officers involved in adultery. The problem is particularly pressing for the Indonesian National Police, as such ethical violations not only undermine the integrity of the institution but also erode public trust and confidence in law enforcement. The study aims to explore the implications of enforcing disciplinary measures for adultery among police members and to identify preventive strategies to mitigate such violations. The research employs a normative juridical methodology, focusing on the implementation of existing legal norms and regulations related to police discipline. This approach involves a thorough examination of formal legal rules, including relevant laws and literature that provide theoretical insights into the subject matter. By correlating these legal frameworks with the issues at hand, the study seeks to provide a comprehensive understanding of how ethical violations are addressed within the Indonesian National Police. The findings reveal that despite the existence of regulations, violations of discipline and ethics, such as adultery, continue to occur frequently among police officers. Factors contributing to this issue include low legal awareness among officers and the influence of their social environment, which weakens the enforcement of discipline. The research suggests several solutions, including enhancing the quality of Police Internal Affairs Investigators, increasing awareness and compliance among police members, and fostering public understanding of disciplinary law enforcement as a means of promoting transparency and accountability.